ANALYSIS OF FARMER’S SATISFACTION TO THE SERVICE QUALITY IN BERINGKIT CATTLE MARKET - I W., SUKANATA; PARIMARTA, I K. W.; PUTRI, B. R. T. (Majalah Ilmiah Peternakan, 2021)
Beringkit cattle market is the largest cattle market in Bali which is expected to shorten the market chain so that farmers get higher prices. However, only a small proportion of them (6.45%) sell their cattle directly to this market. This study aims to determine the level of farmers satisfaction in marketing of their cattle in the Beringkit cattle market based on five dimensions of service quality include tangibility, reliability, responsiveness, assurance and empathy. The data used are primary data collected through interviews with 100 farmers who sell their cows directly in Beringkit cattle market. The data were analyzed using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) methods. The results of this study indicate that the farmers are in the satisfied category in marketing of cattle in the Beringkit Market with a CSI of 76.52%. Based on the IPA analysis, it can be seen that most of the service attributes in the Beringkit Market already have high performance. However, there are also some service attributes that are very important for farmers, but their service performance is still low. These attributes in- clude; place to put livestock, convenience of parking space, responsiveness to farmer complaints, a sense of security from the dangers of livestock, and service costs. Thus, it can be concluded that the quality of service in the Beringkit Market is already good, but the quality of service is still very important to improve.